Project-Based Drawing Activities in Improving Social-Emotional Skills of Early Childhood - Christiani Endah Poerwati; I Made Elia Cahaya (LPPM Universitas Pahlawan Tuanku Tambusai, 2018)
This study aims to improve children's social-emotional abilities through project-based drawing activities. The study was conducted on children of PAUD Pelita Kasih, Dalung group B semester 2 academic year 2017/2018. This type of research is action research with a four-stage procedure, namely: 1) Planning phase, 2) Action taking phase, 3) Development phase, 4) Reflection phase. The research was carried out in two cycles. Data collection methods used in this study are through observation. The process of collecting data through this observation technique uses a rubric guide to record data about the social-emotional abilities shown by early childhood in project-based drawing activities. The results of the study showed an increase in children's social-emotional abilities in project-based drawing activities. Completeness of children's social-emotional abilities in the initial observation of 17 children (68%), the cycle I as many as 19 children (76%), and cycle II 23 children (92%). So it can be said that the project method as an alternative method of learning that is creative, innovative and effective in drawing activities that can improve the social-emotional abilities of early childhood